Faktor Determinan yang Mempengaruhi Stunting pada Anak (usia 0-59 Bulan) di Beberapa Negara Asia Tenggara: English - Rosiyati, Eka; Pratiwi, Erlina A.D.; Poristinawati, Ina; Rahmawati, Erna; Nurbayani, Resita; Lestari, Sri; Wardani, Putri Sari; Nugroho, Muhammad Ridho (LPPM Hang Tuah Pekanbaru, 2018)
Stunting is one of the main nutritional problems caused by malnutrition in children under 5 years old. Risk factors of stunting influenced by socio-economic, Infant and Young Child Feeding (IYCF), child illnesses, Water Sanitaon and Hygiene (WASH). These factors vary considerably accros the nation in southeast asia. The aim of this study was to determine the factors affecting in stunting of children (0-59 months) in Southeast Asia. It is needed to identified the right intervention. This systematic review was conducted using the Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) guidelines. Articles were searched by using pubMed database. The literature search outline in the methods indentified 14.790 arcles discuss stunting. We identified 60 articles potentially met all criteria using PubMed advanced search strategy. A total of 60 articles were retrieved from one database (PubMed), 11 articles met the inclusion criteria for stunting in Southeast Asia countries. In our review socio-economic status was reported as one of consistent factors associated with stunting in Cambodia, Myanmar, Indonesia, Laos, Thailand, and Malaysia. Low household income and lack education of mother influenced inappropriate IYCF practice, poor hygiene and sanitation, and care of child illnesses. Improving like income and maternal exposure to nutrition and health information especially for the topics of growth and development, appropriated IYCF, hygiene, sanitation, and child illnesses are required for continuous improvement in a specific strategy that involves many factors.